Analysis of The Application of The Internal Control System in The Cash Disbursement Procedure For Security Costs Case study: Notary Office Hesti Sulisiati Bimasto, SH - Nurchasannah, Dwi; Ramayanti, Rizka (ADPEBI, 2024)
Internal control of cash disbursements is a process of comparing actual performance with what should be or is planned regarding cash receipt procedures. This research was conducted with the aim of finding out the effectiveness of the implementation of the internal control system for COSO-based cash disbursement procedures at the notary office Hesti Sulistiari Bimasto, SH in Jakarta. The method used in this research is qualitative. Data was obtained from the analysis and interpretation process in accordance with the theory discussed. Primary data was obtained through interviews with the finance department regarding the internal control system in the cash disbursement procedures carried out, while secondary data was obtained in existing form or data already owned by the agency such as invoices, receipts, financial reports and other documents related to cash receipt system. The results of the research reveal that the implementation of the internal control system in cash disbursement procedures at the notary office Hesti Sulistiati Bimasto, SH in Jakarta is still deviant. There are irregularities in the distribution of duties and responsibilities, as well as verification in cash disbursement procedures. Thus, by carrying out this research, it is hoped that the implementation of the internal control system at the notary office Hesti Sulisiati Bimasto, SH, especially the cash receipts accounting system, can be implemented and run well so that the company can achieve its goals.